We have 3z - 1 = z - i + 5. We find z using this.

3z - 1 = z - i + 5

=> 3z - z = 1 + 5 - i

=> 2z = 6 - i

=> z = 3 - i/2

Now the absolute value of z is sqrt [ 3^2 + (1/2)^2]

= sqrt ( 9 + 1/4)

=> sqrt ( 37/4)

=> (sqrt 37) / 2

**The required absolute value is (sqrt 37) / 2**

Posted on

Given 3z -1 = z -i + 5

To find the absolute value, first we need to rewrite z into the form of the complex number z = a + bi.

Let us isolate z on the left side.

==> 3z -1 = z -i + 5

==> 3z = z -i + 6

Now subtract z.

==> 2z = 6 - i

Now we will divide by 2.

==> z = 3 - (1/2)*i

Now that z is in the form a+bi we will calculate the absolute value.

l z l = sqrt(a^2 + b^2)

==> l z l = sqrt(3^2 + (1/2)^2 = sqrt(9+1/4) = sqrt(37/4)

**==> l z l = sqrt37 / 2**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now